Investigation for enhancing the resistance of H-induced delayed cracking for martensitic steel by quenching tempering and quenching partitioning: Influence of microstructure on hydrogen embrittlement and cracking behavior. (26th July 2022) - Wang, Zheng; Wan, Zhongmin; Zhou, Yao; Chen, Xi; Zhang, Jing; Huang, Taiming; Kong, Xiangzhong; Ou, Changjie; Li, Jinxu
Abstract: The objective of the present study is to enhance the hydrogen embrittlement (HE) of the commercial martensitic steel (QT220). For this purpose, the heat treatments of quenching tempering and quenching partitioning are conducted, labeled as QT400 and Q&QP400, respectively. Compared to QT220, the mechanical properties of the both heat-treated specimens are reduced, nevertheless, the HE resistance is extremely promoted, resulting from the lesser dislocations, the more Moy Cx, and the existence of the strained interface of cementite. Besides the above favorable factors, the presence of the ferrite is another important factor which contributes to the lowest HE susceptibility in Q&QP400, resulting from the propagation's inhibition of hydrogen induced cracks (HICs) by ferrite. The HICs behavior of QT220, QT400 and Q&QP400 are mainly influenced by the dislocation glide, the cementite at the high angle boundaries and ferrite, respectively, mainly resulting in the fractographs of quasi-cleavage, intergranular and finely fragmented quasi-cleavage, respectively. In addition, HICs always deflect when propagating to the RD//<112∼114> orientations, providing a valuable direction for research to enhance the HE resistance in the future. Highlights: HE resistance of the martensitic steel is greatly improved by QT and QP. The dispersed ferrite interrupts the continuity of the martensite boundaries. The drop in dislocation density effectively enhances the HE resistance. RD//<112∼114> orientations effectively limit the HICs propagation.